Identification of Type H Vessels in Mice Mandibular Condyle. (August 2021) - Li, H.; Liao, L.; Hu, Y.; Xu, Y.; Zhang, Y.; Huo, F.; Tian, W.; Guo, W.
Type H vessel is a specific vessel subtype that is strongly positive for CD31 and endomucin (CD31 hi Emcn hi ). It has already been identified that it can tightly regulate the coupling of angiogenesis and osteogenesis in the long bone of mice and human beings. The long bone is formed through endochondral ossification, which is the same type of process happening in mandibular condyle. Although the ossification of long bone and mandibular condyle has the same developmental process, the existence of type H vessels in the mouse condyle remains unclear. To address this, we identified that abundant type H vessels existed in the subchondral bone of the mouse condylar head and endosteum of the mouse condylar neck. Meanwhile, immunofluorescence imaging of the condyles in different ages of male C57BL/6J mice demonstrated that type H vessels decreased while aging. Furthermore, we validated a positive correlation between type H vessels and Osterix + osteoprogenitors in the condyle induced by mandibular advancement. Mechanistically, we confirmed that deferoxamine mesylate, which promoted the proliferation of type H endothelial cells by activating hypoxia-inducible factor 1α (HIF-1α) signaling pathways, largely prevented the osteopenia in the condyle induced by botulinum toxin type A. Collectively, these results demonstrate that in the mouse condyle, type H vessels in areas of high function positively correlate with bone formation. In addition, we show a novel influence of HIF-1α signaling on osteogenesis via an increase in type H vessels. In conclusion, promoting angiogenesis of type H vessels is a promising strategy for the therapeutic improvement of osteogenesis in mandibular condyle.